2018
DOI: 10.2214/ajr.17.19350
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Digital Breast Tomosynthesis Adoption on Facility-Level Breast Cancer Screening Volume

Abstract: Objective: To determine whether digital breast tomosynthesis (DBT) adoption was associated with a decrease in screening mammography capacity across Breast Cancer Screening Consortium (BCSC) facilities given concerns about increasing imaging and interpretation times associated with DBT. Materials and Methods: Facility characteristics and examination volume data were collected prospectively from BCSC facilities that adopted DBT between 2011 and 2014. Interrupted time series analyses using Poisson regression mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Second, it was not possible for us to examine facility-level workflow processes that may have influenced selection of women for DBT vs DM screening at the time of their imaging (eg, women with dense breasts may have been preferentially scheduled for DBT screening at some facilities, whereas other facilities may schedule women for the first available mammography machine). 32 Third, we did not account for individual breast cancer risk factors, such as breast density or family history, because a prior analysis 9 demonstrated that use of DBT vs DM did not widely differ based on these risk factors. Finally, the BCSC does not have complete ascertainment of insurance status, preventing us from examining this as an exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, it was not possible for us to examine facility-level workflow processes that may have influenced selection of women for DBT vs DM screening at the time of their imaging (eg, women with dense breasts may have been preferentially scheduled for DBT screening at some facilities, whereas other facilities may schedule women for the first available mammography machine). 32 Third, we did not account for individual breast cancer risk factors, such as breast density or family history, because a prior analysis 9 demonstrated that use of DBT vs DM did not widely differ based on these risk factors. Finally, the BCSC does not have complete ascertainment of insurance status, preventing us from examining this as an exposure.…”
Section: Discussionmentioning
confidence: 99%
“…First, the BCSC captures data only from women who obtain breast imaging, and thus we cannot examine disparities in DBT vs DM use among women who do not undergo routine screening mammography. Second, it was not possible for us to examine facility-level workflow processes that may have influenced selection of women for DBT vs DM screening at the time of their imaging (eg, women with dense breasts may have been preferentially scheduled for DBT screening at some facilities, whereas other facilities may schedule women for the first available mammography machine) . Third, we did not account for individual breast cancer risk factors, such as breast density or family history, because a prior analysis demonstrated that use of DBT vs DM did not widely differ based on these risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…5,[14][15][16][17] There are also challenges linked with using DBT in organised screening programmes, including increased radiation doses, longer reading times for radiologists, increased cost of the technology and increased data storage requirements. 18 We designed the Proteus Donna RCT to prospectively compare DBT with DM in a population-based screening setting. While its primary outcome was to assess the impact of DBT on ICD, the trial design also allowed us to provide a relevant analysis of CD as a cumulative measure over subsequent screening episodes.…”
Section: Introductionmentioning
confidence: 99%
“…However, data relating to how this affects interval cancers detection (ICD) and CD at subsequent screening, and whether it produces overdiagnosis are very limited 5,14‐17 . There are also challenges linked with using DBT in organised screening programmes, including increased radiation doses, longer reading times for radiologists, increased cost of the technology and increased data storage requirements 18 . We designed the Proteus Donna RCT to prospectively compare DBT with DM in a population‐based screening setting.…”
Section: Introductionmentioning
confidence: 99%
“…One might question the usefulness of examining the transition to digital mammography in an era where digital breast tomosynthesis (DBT) is quickly becoming the standard breast cancer screening tool. To date, nearly half of all screening facilities in the United States offer DBT screening (8). In fact, the Tomosynthesis Mammography Imaging Screening Trial (TMIST), a $100 million randomized controlled trial comparing digital mammography to DBT screening, is now underway to compare the effectiveness of DBT to digital mammography (9).…”
mentioning
confidence: 99%